Determination of Nitrite Using UV Absorption Spectra Based on Multiple Linear Regression - Jiao, L.Z.; Dong, D.M.; Zheng, W.G.; Wu, W.B.; Feng, H.K.; Shen, C.J.; Yan, H. (Asian Journal of Chemistry, 2012)
The concentration of nitrite with potential toxicity is an important parameter within environmental, food, industrial and agricultural systems. To determinate nitrite concentration, the method using UV absorption spectra based on multiple linear regression is employed. Principal absorption wavelengths related closely with nitrite concentration are confirmed through analyzing the absorption spectra between the nitrite and nitrate with similar S/N ratio treatment. Utilizing multiple linear regression, mathematical model between absorbance obtained form ten principal absorption wavelengths and nitrite concentration is established. The result shows nitrite concentration between the predicted values and measured values are well coincident when the pH value of nitrite aqueous solution is more than 5 and the related coefficient (R) is 0.9624 over the concentration range 200-2000 ppm. This mathematical model is applied in detecting nitrite concentration of river water and results imply that the system based on this method may be used for on-line determination of the nitrite concentration in the river water.